Looking at them, looking at me. A review of observational studies into the quality of institutional care for elderly people with dementia. - Brooker D (Journal of Mental Health)
The nature of dementia is such that traditional methods of gaining users' views regarding services (interviews, questionnaires, focus groups) cannot be regarded as reliable. Thus, evaluations of care usually include observation of users behaviour and/or the care process. Observational methods employed have varied from study to study but most often attempt to quantify type and levels of residents' activity. Most evaluations are cross-sectional in design and bear witness to the fact that people with dementia living in long-stay settings spend long periods doing nothing. More recent observational techniques such as the Quality of Interactions Scale (QUIS, Dean et al., 1993) and Dementia Care Mapping (Kitwood & Bredin, 1993) attempt to consider the quality as well as the quantity of activity. The latter sets standards of excellence in dementia care but its practical use in improving standards is yet to be fully proven.